Poetyka grozy. Wykorzystanie konwencji gatunkowej horroru w grach cyfrowych - Sikorska, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The aim of the article is to illustrate the using of the horror’s convention in video games and to indicate the way of reinterpretation this convention in the digital medium. In the first part of the work the author presents ways of spaces’ arrangement in survival horror. The analysis of mise-en-scene, including non-interactive cut-scenes, revealed in which ways video games refer to the film genres. In the second part of the work the author analyzes the category of the suspense in the digital medium, taking audial and visual aspects of video game into consideration.